Momentary bursts of cosmic radiation (MAUSAM, 1960)
Continuous records of cosmie ray intensity made by means of ionisation chambers containing gas at atmospheric pressure or at a pressure of several atmosphere as in the apparatus designed by Kolhorster, Hoffmann, Millikan, Compton and others show occasional and momentary, but quite marked increases of ionisation.